Study of Pedestal Column Foundation of Heater Structures After a Fire Accident (Majalah Ilmiah Pengkajian Industri, 2022)
This paper has presented the study of concrete experiencing the fire of the pedestal column of the heater foundation structure after the fire accident. . The evaluation was done with the analytical method, which was conducted to find out the actual condition of an existing structure. Structure or components of the structure are categorized as a safe condition; if its design strength is greater or equal to the required strength or ORn >= Ru. Evaluation of the pedestal column structure with the analytical method was done by visual inspection, concrete quality inspection, cracking depth inspection, structural analysis with the finite element software and strength calculation of structure according to the requirement of SNI 2847 2013. The equipment used for concrete quality inspection is Digischmidt Hammer and PUNDIT. The result showed that there was a degradation of the concrete quality of less than 15%. However, with this condition, all of the pedestal column structures are still in a safe condition in receiving the load operation.  Keywords:  Concrete experiencing a fire, Concrete evaluation, Pedestal column, Required strength, Design strength.